A resolução de problemas de geometria espacial sob a perspectiva dos conceitos Vygotskyanos - Martins, Wesley da Silva (2019)
The present work aroused from my perception of the difficulties teachers face when they teach Spatial Geometry to High School students, and also from my interest to learn new possibilities in order that Mathematics teaching can promote better learning for students. Therefore, the present research aims to use the Methodology of Mathematics Teaching-Learning-Assessment through Problem Solving in the classroom, in the attempt to check the contributions of such methodology for learning Spatial Geometry, in the light of conceptions of zone of proximal development, concepts formation and meaning and sense, proposed by Vygotsky in historical and cultural approach. The qualitative research methodology was used and the data were built through document analysis and participant observation. The investigated documents were the students’ written resolutions for the proposed problems. A sequence of five problems was developed and worked with 35 students of 2nd year of High School in a state school in São Paulo city. The collected and analyzed data showed the work with the Methodology of Mathematics Teaching-Learning- Assessment through Problem Solving gives teachers more consistent knowledge of their students’ learning process and makes them more able to help them. It gave students the opportunity to learn the contents related to Spatial Geometry, so that the development of geometric learning favored the recognition of relevant attributes of flat and spatial figures, perception and understanding of relations, appropriation of language and geometric nomenclature. It highlighted to the researcher the development of skills that help students understand and interpret the world around them, as well as skills to solve problems of any kind, such as experimentation, elaboration of conjectures, mathematical formalization, among others.